Implementasi Inovasi Pembelajaran Geografi Tingkat SMA Dalam Kurikulum 2013 - Detty Wijayanti; Syafri Anwar; Khairani Khairani; Nola Aprilia Sukhaimi (Departement of Mathematics Education, 2022)
This article contains ideas about the implementation of high school level geography learning innovations in the 2013 curriculum as the heart of education and guidelines for learning. Geography is a science that studies the causal relationship of various phenomena and events that occur on earth, both physically and involving living things and their problems through spatial, ecological, and regional approaches. The results of the geographical study are directed to the interests of the program, process, and success of development. In the 2013 curriculum, geography subjects are grouped in the Social Sciences Specialization Subject cluster so that the study is more directed at the point of view of human existence and activities which are influenced by the dynamics of the physical nature. As a competency-based curriculum, the Geographys’ subject is set to have four Core Competencies (KI), namely competence in the aspect of living and practicing religious teachings, competence in affective aspects, competence in cognitive aspects, and competence in psychomotor aspects. Related to the study in this paper, curriculum makers must consider the scope and sequence aspects. The arrangement of geography material, both in scope and in sequence, will have an impact on the level of understanding and the knowledge construction process of students.